Subspecies and Distribution. L. c. canadensis Kerr, 1792 — mainland Canada and N USA. L. c. subsolanus Bangs, 1897 — NE Canada (Newfoundland I). in Felidae - Wilson, Don E.; Mittermeier, Russell A. (Zenodo, 2009)
Subspecies and Distribution. L. c. canadensis Kerr, 1792 — mainland Canada and N USA. L. c. subsolanus Bangs, 1897 — NE Canada (Newfoundland I). : Published as part of Don E. Wilson & Russell A. Mittermeier, 2009, Felidae, pp. 54-168 in Handbook of the Mammals of the World – Volume 1 Carnivores, Barcelona :Lynx Edicions on page 150, DOI: 10.5281/zenodo.6376899